Age-dependent impairment of eyeblink conditioning in prion protein-deficient mice. - Yasushi Kishimoto; Moritoshi Hirono; Ryuichiro Atarashi; Suehiro Sakaguchi; Tohru Yoshioka; Shigeru Katamine; Yutaka Kirino (PLoS ONE, 2013)
Mice lacking the prion protein (PrP(C)) gene (Prnp), Ngsk Prnp (0/0) mice, show late-onset cerebellar Purkinje cell (PC) degeneration because of ectopic overexpression of PrP(C)-like protein (PrPLP/Dpl). Because PrP(C) is highly expressed in cerebellar neurons (including PCs and granule cells), it may be involved in cerebellar synaptic function and cerebellar cognitive function. However, no studies have been conducted to investigate the possible involvement of PrP(C) and/or PrPLP/Dpl in cerebellum-dependent discrete motor learning. Therefore, the present cross-sectional study was designed to examine cerebellum-dependent delay eyeblink conditioning in Ngsk Prnp (0/0) mice in adulthood (16, 40, and 60 weeks of age). The aims of the present study were two-fold: (1) to examine the role of PrP(C) and/or PrPLP/Dpl in cerebellum-dependent motor learning and (2) to confirm the age-related deterioration of eyeblink conditioning in Ngsk Prnp (0/0) mice as an animal model of progressive cerebellar degeneration. Ngsk Prnp (0/0) mice aged 16 weeks exhibited intact acquisition of conditioned eyeblink responses (CRs), although the CR timing was altered. The same result was observed in another line of PrP(c)-deficient mice, ZrchI PrnP (0/0) mice. However, at 40 weeks of age, CR incidence impairment was observed in Ngsk Prnp (0/0) mice. Furthermore, Ngsk Prnp (0/0) mice aged 60 weeks showed more significantly impaired CR acquisition than Ngsk Prnp (0/0) mice aged 40 weeks, indicating the temporal correlation between cerebellar PC degeneration and motor learning deficits. Our findings indicate the importance of the cerebellar cortex in delay eyeblink conditioning and suggest an important physiological role of prion protein in cerebellar motor learning.